Beyond society's desire for a slowed-down temporal experience: Toward a nomological network of individuals' need-for deceleration - Anna-Lena Sager; Jule Timm; Stefan Hoffmann; Ulrich R. Orth (Psychology & Marketing, 2023)
This study expands on past deceleration and slow consumption research by introducing and validating a measure of need-for-deceleration, an individual's motivational ability to engage in activities aimed at slowing down the perceived fast passage of time. Following initial scale development, two studies establish construct validity by placing need-for-deceleration into a nomological network. Results indicate that the measure correlated with, but was distinct from, variables involving negative affective states, such as state anxiety and neuroticism. Need-for-deceleration scores were not related to materialism, but negatively correlated with self-efficacy, life satisfaction, work-life balance, and conscientiousness. Correlations were positive with need-for-uniqueness, future time orientation, and susceptibility to normative influence. Need-for-deceleration was also associated with regulatory focus (positively with prevention, and negatively with promotion focus). To explore criterion validity, a third study establishes associations between need-for-deceleration and consumer lifestyle variables. Developing and validating the scale can help researching and managing products relating to the consumption of time, wellness, mindfulness, and simplicity.
Keywords: 650; life satisfaction; motivation; need-for-deceleration; personality architecture; self; well-being; work-life-balance